2011
DOI: 10.1111/j.1365-2044.2011.06700.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of analgesic efficacy of subcostal transversus abdominis plane blocks with epidural analgesia following upper abdominal surgery

Abstract: SummarySubcostal transversus abdominis plane (TAP) catheters have been reported to be an effective method of providing analgesia after upper abdominal surgery. We compared their analgesic efficacy with that of epidural analgesia after major upper abdominal surgery in a randomised controlled trial. Adult patients undergoing elective open hepatobiliary or renal surgery were randomly allocated to receive subcostal TAP catheters (n = 29) or epidural analgesia (n = 33), in addition to a standard postoperative analg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
164
1
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(179 citation statements)
references
References 19 publications
5
164
1
9
Order By: Relevance
“…Only three studies [41][42][43] addressed the comparison between TAP block and epidural anesthesia, and none of them showed any significant differences between the two techniques ( Table 2). Only one RCT 43 investigated eight-hour pain score, and one trial 43 reported the 24-hr morphine consumption.…”
Section: Transversus Abdominal Plane Block Vs Epidural Analgesiamentioning
confidence: 99%
See 1 more Smart Citation
“…Only three studies [41][42][43] addressed the comparison between TAP block and epidural anesthesia, and none of them showed any significant differences between the two techniques ( Table 2). Only one RCT 43 investigated eight-hour pain score, and one trial 43 reported the 24-hr morphine consumption.…”
Section: Transversus Abdominal Plane Block Vs Epidural Analgesiamentioning
confidence: 99%
“…16,29,36,38,[40][41][42][43]52 Compared with the control group, TAP block showed no difference in reducing the six-hour pain score 16,29,36,38,41,43 (-0.1; 95% CI, -1.4 to 1.3; P = 0.95), 12-hr pain score 16,38,41,52 (1.9, 95% CI, -4.2 to 0.4; P = 0.11), 24-hr pain score 16,29,36,38,[41][42][43]52 (-0.8; 95% CI, -2.0 to 0.4; P = 0.18), or 24-hr morphine consumption 16,29,36,38,43,52 (-14.7 mg; 95% CI, -37.8 to 8.4; P = 0.21) ( Table 2). Only one trial 16 performed TAP block from inside the abdominal wall; consequently, it was not possible to perform subgroup analysis for this comparison.…”
Section: Transversus Abdominal Plane Block In Abdominal Surgerymentioning
confidence: 99%
“…Therapeutic failure rate was higher in the epidural group, and the incidence of hypotension was also greater (Kadam 2011). Niraj et al are also amongst the few having compared the new techniques versus the older and more established techniques (Niraj 2011). Dr. Niraj compared the analgesic efficacy of the subcostal TAP block catheter technique (very much resembling the technique described by Dr. Hebbard) with the epidural analgesia for patients undergoing elective open hepatobiliary or renal surgery.…”
Section: Analgesic Efficacy Of Truncal Blocks Compared To Epidural Anmentioning
confidence: 99%
“…Although laparoscopic cholecystectomy is less invasive than open cholecystectomy, it is still associated with significant moderate to severe pain during the first 24 hours after surgery, especially at trocar insertion sites [6,7]. During laparoscopic cholecystectomy these sites are innervated by nerves from T6 to L1 at the neurovascular plane of the abdominal wall [4,5], and thus, it might be expected that TAP blocks would be useful for controlling pain after laparoscopic cholecystectomy.…”
Section: Introductionmentioning
confidence: 99%